ANALYSIS LAYER MODEL OF POLYMER COMPOSITE DESIGN UNDER MULTIFACTOR LOADING - Oleg G. Osyaev; Yury A. Taturin; Alexey M. Kostin; Artur V. Zhukov (Advanced Engineering Research)
A mathematical model is offered for the analysis of complex stress-strain state of the layer load-carrying structures of the aircraft planes. It is presented as sets of the equations of the constraining relations of load parameters, voltages and deformation. The complex multilayered solution method that allows including specific features of the design geometry and behaviour of structural materials through multifactor loading is used for the solution of the systems of the equations.